Continuous background light significantly increases flashing-light enhancement of photosynthesis and growth of microalgae. (July 2015) - Abu-Ghosh, Said; Fixler, Dror; Dubinsky, Zvy; Iluz, David
Graphical abstract: Highlights: A novel efficient light regime for increasing photosynthesis and algae growth. Using continuous background light significantly enhances the flashing light effect. The light combination-regime can be used with any light intensity. This strategy is simple and applicable in all microalgae bioreactors. Abstract: Under specific conditions, flashing light enhances the photosynthesis rate in comparison to continuous illumination. Here we show that a combination of flashing light and continuous background light with the same integrated photon dose as continuous or flashing light alone can be used to significantly enhance photosynthesis and increase microalgae growth. To test this hypothesis, the green microalga Dunaliella salina was exposed to three different light regimes: continuous light, flashing light, and concomitant application of both. Algal growth was compared under three different integrated light quantities; low, intermediate, and moderately high. Under the combined light regime, there was a substantial increase in all algal growth parameters, with an enhanced photosynthesis rate, within 3 days. Our strategy demonstrates a hitherto undescribed significant increase in photosynthesis and algal growth rates, which is beyond the increase by flashing light alone.